2018
DOI: 10.1038/s41588-018-0161-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer hubs and loop collisions identified from single-allele topologies

Abstract: Chromatin folding contributes to the regulation of genomic processes such as gene activity. Existing conformation capture methods characterize genome topology through analysis of pairwise chromatin contacts in populations of cells but cannot discern whether individual interactions occur simultaneously or competitively. Here we present multi-contact 4C (MC-4C), which applies Nanopore sequencing to study multi-way DNA conformations of individual alleles. MC-4C distinguishes cooperative from random and competing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
168
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(192 citation statements)
references
References 46 publications
(32 reference statements)
20
168
0
Order By: Relevance
“…Recent technologies enabling the study of three-way 33 or higher-order chromatin interactions include chromosomal walks (c-walks) 34 , genome architecture mapping (GAM) 35 , split-pool recognition of interactions by tag extension (SPRITE) 36 , ChIA-drop 37 , Tri-C 38 , Tethered multiple 3C 39 , the concatemer ligation assay (COLA) 33 and Multicontact 4C (MC-4C) 40 . Among these assays, only a subset (Tri-C, SPRITE, COLA, GAM) have been shown to generate genome-wide maps in mammals, and all methods but SPRITE suffer from very rare representation of (<1%) of contacts with order >3 36 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent technologies enabling the study of three-way 33 or higher-order chromatin interactions include chromosomal walks (c-walks) 34 , genome architecture mapping (GAM) 35 , split-pool recognition of interactions by tag extension (SPRITE) 36 , ChIA-drop 37 , Tri-C 38 , Tethered multiple 3C 39 , the concatemer ligation assay (COLA) 33 and Multicontact 4C (MC-4C) 40 . Among these assays, only a subset (Tri-C, SPRITE, COLA, GAM) have been shown to generate genome-wide maps in mammals, and all methods but SPRITE suffer from very rare representation of (<1%) of contacts with order >3 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies combining targeted chromatin conformation capture with long-read sequencing have revealed that many of the products of proximity ligation are in fact DNA "concatemers" of multiple interacting loci 33,34,37,40,41 . We surmised that chromatin conformation capture could be paired with nanopore sequencing to efficiently assay the combinatorial chromatin structure in human cells ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As cells differentiate further, these interactions are strengthened, concomitant with strong upregulation of gene activity. It has recently been shown for the globin loci that gene activation is associated with the formation of higher-order hub-like structures, in which multiple enhancers and promoters form simultaneous, specific interactions 23,31 . Our data suggest that these structures may only be formed in the final stage of differentiation, when chromatin accessibility and interactions between enhancers and promoters are strongest, and may be important to achieve maximal gene expression.…”
mentioning
confidence: 99%
“…The method is based on conventional chromosome conformation capture (3C) 10 and the C-walk and multi-contact 4C approaches developed earlier [11][12][13] . 3C performed with the restriction enzyme DpnII produces long ligation products where multiple restriction fragments become ligated together to form DNA molecules that can be >6 kb long, and that are mostly linear (Supplemental Figure 1).…”
Section: Resultsmentioning
confidence: 99%